Empowerment of students at SMP 1 Muhammadiyah Klaten as peer educators on reproductive health for adolescents - Syahputri, Rezyana Budi; Prakosa, Farid Aji; Purnamasari, Salsabila Aulia; Maresta, Arista Siti (Nur Science Institute, 2024)
Adolescence is a phase of life where individuals experience significant development, including sexual changes, during the ages of 13-15. Middle school students often hesitate to discuss reproductive health with their parents, preferring instead to share information with their peers. Peers, acting as peer educators, play a crucial role in influencing adolescents' attitudes, clothing styles, and social behavior. This community service aimed to provide information on reproductive health to students at SMP 1 Muhammadiyah Klaten to enhance their ability to spread this information to others. The methods used included the development of a pocketbook, coordination with the school, a pre-test, information delivery, a post-test, and understanding the role of a peer educator. The results showed improvements in knowledge and attitudes regarding reproductive health. In conclusion, providing information about adolescent reproductive health is effective in developing peer educators.